First record of the Ravinia almeidai (Lopes, 1946) (Diptera: Sarcophagidae: Sarcophaginae) to the state of Bahia, Brazil - Ramos, Ramon L.; Trindade-Santos, Matheus E.; Lopes, Daniele S.; Pamponet, Fernanda M.; Mello-Patiu, Cátia A. de; Oliveira, Favízia F. de (Entomological Communications, 2021)
The first record of Ravinia almeidai (Lopes, 1946) is reported for the state of Bahia, northeast region of Brazil. The record of this fly species significantly contributes to the knowledge of sarcophagids from the northeast, as well as to the mapping of its distribution in the Brazilian territory.